Rio+20: Searching for sustainable development - Sanchez Alvarez, Melissa (2012)
This article seeks to deepen the importance of the recent Earth Summit Rio+20, conducted this past June. Special emphasisis placed on the different points of view around the central issues of the debate and on the relevance of the conclusionsreached.